The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1177/073490402762574767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-halogen Flame Retardant Additives on the Properties of Vinyl Ester Resins and their Composites

Abstract: The paper describes the effect of combination of char forming additives and char forming catalysts on limiting oxygen index (LOI), smoke density and mechanical properties of neat as well as glass fibre reinforced vinyl ester (VE) resins. Three different samples of VE resins were prepared by reacting diglycidyl ether of bisphenol-A and methacrylic acid in stoichiometric (1 : 2, sample A) and non-stoichiometric (1 : 1.7, sample B and 1 : 1, sample C) amounts. These resins were diluted with reactive diluents (50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The mechanical properties of fibrous composites, such as tensile strength and modulus, flexural strength and modulus, interlaminar shear strength, compressive strength, etc., depends on the structure of matrix resins, properties of fibers, volume fraction of fibers ( V f ), and interphase. The structure of cross‐linked network of VE can be altered by changing the backbone structure or end groups or the nature and concentration of reactive diluents (e.g., styrene) 6, 7. Higher interlaminar shear strength of glass fiber‐ reinforced laminates was observed in our earlier studies with VE containing one epoxy end group 6.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The mechanical properties of fibrous composites, such as tensile strength and modulus, flexural strength and modulus, interlaminar shear strength, compressive strength, etc., depends on the structure of matrix resins, properties of fibers, volume fraction of fibers ( V f ), and interphase. The structure of cross‐linked network of VE can be altered by changing the backbone structure or end groups or the nature and concentration of reactive diluents (e.g., styrene) 6, 7. Higher interlaminar shear strength of glass fiber‐ reinforced laminates was observed in our earlier studies with VE containing one epoxy end group 6.…”
Section: Introductionmentioning
confidence: 77%
“…The structure of cross‐linked network of VE can be altered by changing the backbone structure or end groups or the nature and concentration of reactive diluents (e.g., styrene) 6, 7. Higher interlaminar shear strength of glass fiber‐ reinforced laminates was observed in our earlier studies with VE containing one epoxy end group 6. Styrene imparts good mechanical properties (i.e., tensile strength), heat distortion resistance, and dielectric properties to cured resins 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies have indicated that curing characteristics are affected by the presence of oxirane groups in VE resins. 11,12 The oxirane functionality in the resin also provides an additional site for reaction with amines 13 or carboxylic acids. 2 Higher interlaminar shear strength of glass fiber reinforced laminates was observed when resins containing oxirane rings were used.…”
Section: Introductionmentioning
confidence: 99%
“…2 Higher interlaminar shear strength of glass fiber reinforced laminates was observed when resins containing oxirane rings were used. 13 Therefore, synthesis and characterization of mono(meth)acrylate resins prepared by reacting equimolar amounts of ER and unsaturated carboxylic acid was also carried out. The main objective of these studies was to synthesize, characterize, and evaluate thermal behavior of the VE resins containing cycloaliphatic moieties.…”
Section: Introductionmentioning
confidence: 99%